Sentiment Analysis of Social Media and its Implications for Corporate Governance and Financial Misreporting - Nur Anindhita Kurniawaty Wijaya (Journal of Business Crime, 2025)
Objective: This study discusses various literature reviews of the findings of various previous studies that discuss social media sentiment analysis to explore the potential of analyzing predictors of financial misreporting and financial governance. Research Design & Methods: This research uses a qualitative method by analyzing various article findings that discuss social media-based sentiment analysis. Consists of collecting, categorizing, analyzing data and conclusions. Findings: The results of this study offer significant benefits to companies and investors. The use of sentiment analysis allows market participants to more accurately predict stock price movements, especially during periods of high volatility or crisis. In addition, sentiment data from social media helps in identifying corporate credit risks and responding to negative sentiment trends that could be detrimental to the company. Implications: This research provides important insights into marketing strategies, where companies can customize their campaigns based on changes in consumer perceptions reflected by social media. Contribution: The use of social media as a financial reporting tool can increase transparency and expand audience reach, but it also raises new challenges in terms of regulatory compliance.